1992 BUDGET PUBLIC AFFAIRS DIVISION COST CENTER GENERAL COALITIONS NO. 1307 (Tufts Archival Research Center, 2007)
Confidential; Tobacco Institute's 1992 Budget from the Public Affairs Division. Highlights expenses for general coalitions and gives detailed expenses for travel, postage and delivery, reproduction, printing and drafting, membership and staff training, professional fees, advertising, and support of other tobacco organizations.